Conditional Vascular Cell Adhesion Molecule 1 Deletion in Mice: Impaired Lymphocyte Migration to Bone Marrow - Koni, Pandelakis A. (The Rockefeller University Press, 2001)
We generated vascular cell adhesion molecule (VCAM)-1 “knock-in” mice and Cre recombinase transgenic mice to delete the VCAM-1 gene (vcam-1) in whole mice, thereby overcoming the embryonic lethality seen with conventional vcam-1–deficient mice. vcam-1 knock-in mice expressed normal levels of VCAM-1 but showed loss of VCAM-1 on endothelial and hematopoietic cells when interbred with a “TIE2Cre” transgene. Analysis of peripheral blood from conditional vcam-1–deficient mice revealed mild leukocytosis, including elevated immature B cell numbers. Conversely, the bone marrow (BM) had reduced immature B cell numbers, but normal numbers of pro-B cells. vcam-1–deficient mice also had reduced mature IgD(+) B and T cells in BM and a greatly reduced capacity to support short-term migration of transferred B cells, CD4(+) T cells, CD8(+) T cells, and preactivated CD4(+) T cells to the BM. Thus, we report an until now unappreciated dominant role for VCAM-1 in lymphocyte homing to BM.